Site-specific Fertilizer Nitrogen Management in Irrigated Wheat using Chlorophyll Meter (SPAD meter) in the North-western India - Yadvinder-Singh, Ajay-Kumar, Sandeep Sharma*, H.S. Thind, O.P. Choudhary and Monika Vashis, Bijay-Singh, Varinderpal-Singh (Journal of the Indian Society of Soil Science, 2018)
In irrigated wheat as grown in north-western India, fertilizer nitrogen (N) management following blanketrecommendations is increasing resulting in stagnant yield levels with low N use efficiency. Site-specificnutrient management strategy to apply N as per need of wheat crop was formulated based on leaf colourmeasured by chlorophyll meter (Minolta SPAD meter) as a function of soil N supply. The SPAD meterguidedprotocols for fertilizer N application at crown root initiation (CRI) and maximum tillering (MT)stages, coinciding with first two irrigations, were evaluated through a series of field experiments with sevenwheat varieties in Ludhiana and Gurdaspur in north-western India. Threshold leaf greenness levels equivalentto SPAD readings